Market segmentation to become the partner of choice - Deines, Tara (Kansas State University, 2014)
The agriculture industry has been a dynamic industry exploding with change in recent years. The world has experienced extreme population growth, along with shifts in social status, dietary habits, and consumption patterns that have led to a rapidly growing and changing agriculture industry demanding increasing grain production. The expected pace of production necessary to continue to feed the world has heightened the competition in the agriculture industry. This study focuses on analyzing how Company XYZ, a strong competitor in the grain and ethanol industry, can leverage the opportunities that the growth of the agriculture industry has provided. In order to maximize opportunities with each customer and remain competitive in new territories, the need is presented to develop a repeatable process. This process will focus on determining how to interpret customer preferences to quickly make the company the first preference of choice for target customers as they grow further into North America and beyond. This thesis will focus on understanding and operationalizing two components. First, identifying the most desirable customers and what makes them desirable. Secondly, understanding, anticipating, and consistently addressing the needs of customers to address them better than the competition. To analyze and understand customer habits and behaviors this thesis examines the results of a survey conducted with existing customers. Regression analysis of the overall profitability of a customer to the company and a regression analysis of the customer's ratings of Company XYZ in relation to the competition were used to help identify how the discrimination and segmentation factors impact each regression. A cluster analysis is also implemented with the survey data to segment customers in order to develop a structured plan that can be implemented within the business practices. The cluster analysis revealed three dominant clusters that customers can be segmented into. These clusters, in conjunction with the findings from the regression analyses, help identify areas of strength and weakness to develop a plan of action for Company XYZ to implement. The plan, known as the Partner of Choice, directs the focus on implementing market segmentation to leverage customized marketing opportunities, behavioral management alignment, employee incentive opportunities, and a structured training program.
Keywords: Market segmentation; Customer survey; Grain; Cluster analysis; Regression; Competitors